Expansion of circulating extrafollicular helper T-like cells in patients with chronic graft-versus-host disease. (June 2019) - Jin, Hua; Yang, Kaibo; Zhang, Haiyan; Chen, Yanqiu; Qi, Hanzhou; Fan, Zhiping; Huang, Fen; Xuan, Li; Lin, Ren; Zhao, Ke; Liu, Qifa
Abstract: Chronic graft-versus-host disease (cGVHD) is a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Previous studies have shown that T follicular helper cells (Tfh) contribute to immune pathology in cGVHD, but the function of extrafollicular helper T cells during cGVHD pathogenesis remains largely unknown. In the current study, we identified circulating extrafollicular helper T-like cells (CD44 hi CD62L lo PSGL-1 lo CD4 +, c-extrafollicular Th-like) in human peripheral blood. We performed phenotypic and functional analyses of c-extrafollicular Th-like cells from 80 patients after allo-HSCT to explore the role of these cells in the development of human cGVHD. Patients with active cGVHD had significantly higher frequencies and counts of c-extrafollicular Th-like cells than those of patients without cGVHD. The expansion of c-extrafollicular Th-like cells was more significant in patients with moderate/severe cGVHD than that of patients with mild cGVHD. C-extrafollicular Th-like cells from patients with active cGVHD exhibited increased functional abilities to induce plasmablast differentiation and IgG1 secretion compared to those of patients without cGVHD. Moreover, c-extrafollicular Th-like cell levels were highly correlated with the generation of autoreactive B cells, plasmablasts and IgG1 antibodies. Our studies provide new insights into human cGVHD pathogenesis and identify c-extrafollicular Th-like cells as a key element in the development of human cGVHD. Highlights: Circulating extrafollicular helper T-like cells expand in patients with cGVHD. C-extrafollicular Th-like cells correlate with the generation of plasmablasts. C-extrafollicular Th-like cells correlate with the generation of IgG1 antibodies.